THE GENDER AND AGE FEATURES OF REPRESENTATIONS ABOUT BULLYING AMONG SCHOOL STUDENTS - Kalinina, Rumia; Gribanova, Diana; Maksimenkova, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article is devoted to the analysis of the gender and age features of the representations about bullying among school students. Bullying is seen as a serious socio-psychological problem. Presented the program and methods of the empirical study of bullying in the educational environment. The results of this study are analized.